Tire tracks and tread marks - Given, Bruce W. (Houston Gulf Publishing Company, 1977)
Its a handbook of procedures for processing track and tread evidence so that it can be of real investigative value, and not just a courtroom exhibit. There is a considerable body of knowledge on track scene reconstruction.
Keywords: Law